The lacustrine deposits of Fornaci di Ranica (late Early Pleistocene, Italian Pre-Alps): stratigraphy, palaeoenvironment and geological evolution - RAVAZZI C.; PINI R.; MARTINETTO E.; MUTTONI G.; CHIESA S.; CONFORTINI F.; EGLI R.; BREDA, Marzia (Quaternary International, 2005)
An interdisciplinary investigation of the Pleistocene succession of Fornaci di Ranica (Italian Pre-Alps) aimed to reconstruct the palaeoenvironmental history and its chronostratigraphic position and to consider the implications for the Quaternary evolution of the southern alpine border near the Early/Middle Pleistocene transition. A detailed survey of Quaternary deposits in boreholes and exposed sections provided a complete record of the basin. The most complete core was analyzed for palynology and magnetic properties. Plant macrofossils were obtained by flotation. Pollen and spectrometric analysis allowed a precise stratigraphic placement of a moose antler and braincase kept in museum collections. The basin originated from fluviatile obstruction of a tributary valley cut into bedrock. The basal deposits formed as a terrestrial hydromorphic soil under a dense Tsuga-forest (zone RNC 1). The overlying palustrine gyttja shows a marked forest withdrawal with a climatic signature (zone RNC 3), followed by a re-establishment of mixed conifer forests (zones RNC 4 to 6). The occurrence of pollen of arctic-alpine (Pinguicula, Saxifraga oppositifolia type) and other cold-adapted taxa (Saxifraga stellaris type, Larix), is the oldest so far known south of the Alps and suggests that mean summer temperature was near or even below the thermic tree limit. High herb diversity, partially referable to tall forbs, characterizes this zone. A further increase of water table can be assumed in the interval RNC 4 and RNC 5, as suggested from the expansion of pollen of aquatic plants. The find of Larix decidua L. cones demonstrates the existence of the European larch in the Early Pleistocene of the Alps, previously not identified at the species level. After the Serio river had reached the maximum Quaternary aggradation, the lake was rapidly filled up with turbiditic sediments. The identification of Cervalces latifrons (Johnson, 1874) by Azzaroli (1979) was confirmed. Pollen spectra obtained from clay fragments preserved in the braincase ...